War and Armed Conflict in the Information Space - Labush, Nikolai Sergeevich; Nikonov, Sergey Borisivich; Puiy, Anatoli Stepanovich; Georgieva, Elena Savova; Bekurov, Ruslan Viktorovich (International Review of Management and Marketing, 2015)
New generation of wars is characterized by the effective application of information – from information and combat actions support to the actual information war. Sociopolitical processes are impacted by means of mediatization. Acquiring specific content, noopolitics becomes an important activity of government institutions. It seems to have the capability to realize national interests and information security. The article identifies the distinctive features of information support of combat actions and information war as a product of the mass-media technology. The authors aim to identify the specificity of mass media war and criteria for its manifestation. Keywords: information war, mass media, mass-media war, armed conflict JEL Classifications: D83; F52; O31; O33; O38